Dedication to the craft: developing pre-service teachers into social justice advocates through PDS and poetry - Kerry Cormier (Emerald Publishing, 2023)
Purpose - The purpose of this poetic inquiry was to understand how the professional development school (PDS) model can help pre-service teachers (PSTs) develop an inclusive philosophy of teaching while positioning themselves as social justice advocates. Four clinical interns collaborated in the research process guided by the university professor-in-residence (PIR). Design/methodology/approach - To conduct this poetic inquiry the interns kept journals, participated in individual interviews and weekly book club discussions to help us understand how education is situated within a broader social justice framework. Transcription poems were created from discussion and interview transcripts to capture the interns' perspectives and experiences in developing their philosophies. Findings - The findings, shared through transcription poems, indicate that the interns established inclusive beliefs, experienced tensions between their beliefs and practices and emphasize the importance of community in developing as social justice advocates. Originality/value - By sharing the findings through poetry, this study invites a more focused look into the nuances of PST's emerging beliefs on inclusive education in a PDS.